2013
DOI: 10.1108/ijhcqa-09-2011-0054
|View full text |Cite
|
Sign up to set email alerts
|

Six Sigma in healthcare delivery

Abstract: This article comprehensively assesses Six Sigma healthcare applications and impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 59 publications
2
57
0
2
Order By: Relevance
“…Complex processes, in which variability is likely to be high, lend themselves well to LSS methodology that focuses on reducing variables and defects. 15 To the best of our knowledge, from Pubmed searches up until June 1, 2016, this is the first study to show that LSS can be used to reduce the rate of cesarean sections. Our study demonstrated that LSS successfully reduced cesarean section rate by 9.8%, from 41.8% to 32%, with an increase in Six Sigma score from 1.704 to 1.967 (P < .001).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Complex processes, in which variability is likely to be high, lend themselves well to LSS methodology that focuses on reducing variables and defects. 15 To the best of our knowledge, from Pubmed searches up until June 1, 2016, this is the first study to show that LSS can be used to reduce the rate of cesarean sections. Our study demonstrated that LSS successfully reduced cesarean section rate by 9.8%, from 41.8% to 32%, with an increase in Six Sigma score from 1.704 to 1.967 (P < .001).…”
Section: Discussionmentioning
confidence: 92%
“…The process of cesarean section reduction is complex, requiring the coordination of several different groups including pregnant women, obstetricians, anesthetists, and midwives. Complex processes, in which variability is likely to be high, lend themselves well to LSS methodology that focuses on reducing variables and defects . To the best of our knowledge, from Pubmed searches up until June 1, 2016, this is the first study to show that LSS can be used to reduce the rate of cesarean sections.…”
Section: Discussionmentioning
confidence: 97%
“…Six Sigma and lean theory, for example, focus on identifying the weaknesses and inefficiencies of existing systems. 12 These methods can overlook what a system does well; in our study, we identified three processes that did not need improvement along with seven that did. Our experience exemplified the ability of the systems approach to deconstruct a service to its most necessary components and detect both strengths and weaknesses.…”
Section: Discussionmentioning
confidence: 93%
“…Berbagai penelitian implementasi Six Sigma sudah dilakukan di berbagai bidang dan telah memberikan hasil yang perbaikan signifikan seperti manufaktur (Indrawati & Ridwansyah, 2015), pendidikan (Patil, Kamlapur, & Dhore, 2006), kontruksi (Han, Chae, Im, & Ryu, 2008), perbankan (Putri, Gunawan, & Sutanto, 2017), dan kesehatan (J. Liberatore, 2013).…”
Section: Pendahuluanunclassified